A Retrospective Study on the Risk of Non-Melanoma Skin Cancer in PUVA and Narrowband UVB Treated Patients - P, Darukarnphut; P, Rattanakaemakorn; N, Rajatanavin (Archives of Clinical and Biomedical Research, 2017)
Background: Narrow-band ultraviolet B (NB-UVB) and Psoralen-UVA (PUVA) phototherapy are widely used as the treatment of dermatologic diseases. The carcinogenic risk associated with NB-UVB and PUVA phototherapy treatment is unknown. Objective: To determine the non-melanoma skin cancer risk in a patients treated with Narrow-band ultraviolet B (NB-UVB) and Psoralen-UVA (PUVA) phototherapy. Methods: All Narrow-band ultraviolet B (NB-UVB) and Psoralen-UVA (PUVA) phototherapy treated patient records who received the phototherapy in Ramathibodi Hospital from 2001 to 2015 were reviewed. Results: A total of 726 with Narrow-band ultraviolet B (NB-UVB) and Psoralen-UVA photochemotherapy (PUVA) phototherapy treated patients with mean age of 46.7 years. Most of patients have skin phototypes III to IV. Vitiligo is the most common disease treated with phototherapy (43.8%). The median number of NB-UVB treatment was 126 treatments with cumulative dose 94.2 J/cm². The median number of PUVA treatment was 103 treatments with cumulative dose 249.2 J/cm². There was no non melanoma skin cancer in our patients. The median time of follow up was 28.4 months. Conclusion: This study did not shown an increase risk of skin cancer in patients who had receiving long term NBUVB and PUVA phototherapy. We suggest that long term NB-UVB and PUVA phototherapy are safe therapeutic modalities for the patients with skin phototypes III to IV.